Dang Hyang Astapaka and his Cultural Geography in Spreading Spreading Vajrayana Buddhism in Medieval Bali - Bagus, Ida; Suamba, Putu (Journal of International Buddhist Studies, 2016)
The sway of Hinduism and Buddhism in Indonesia archipelago had imprinted deep cultural heritages in various modes. The role of holy persons and kings were obvious in the spread of these religious and philosophical traditions. Dang Hyang Asatapaka, a Buddhist priest from East Java had travelled to Bali in spreading Vajrayana sect of Mahayana Buddhist in 1430. He came to Bali as the ruler of Bali invited him to officiate Homa Yajna together with his uncle Dang Hyang Nirartha, who had stayed earlier in Bali. Impressed with deep knowledge and spiritual acumen of him, the ruler Waturenggong King appointed him as a purohito (priest palace), whose jobs were to give spiritual consultation and political advisor in ruling the country. During his life times in Bali, he travelled from one place to another spreading Vajrayana sect of Buddhism. Lastly he settled in Budakeling village in East Bali where he built gerya (house) and temples for worship and meditation. Form here he, his descents, and followers spread the Vajrayana to all over Bali and Lombok.He left us with Vajrayana sect of Buddhism, which was assimilated with Saivism. Dang Hyang Astapaka and his uncle Dang Hyang Nirartha were the advocators of Saiva-Buddha cult in Bali backed up by the rulers.